Were the oasis-cities of the southern branch of the Silk Road in Tarim Basin, China, dispersed urban complexes? - Hanus , Kasper (Folia Praehistorica Posnaniensia, 2021)
This article reinterprets the urban pattern of the oases of southern Tarim Basin, which flourished in the first half of the first millennium C.E. using the dispersed urban complexes framework. Disperse urban centre, also known as a low-density urban complex, is a site that had an urban function, but its morphology was much different from compact cities of, for example, China or mediaeval Europe. Low-density urban complexes, like Tikal in Mesoamerica or Angkor in South-East Asia, despite their distinct urban functions, had the cityscape consisting of intermingled monumental agriculture, water management features and agricultural field. Thus, the oasis-cities of southern Tarim Basin were different from compact urban centres of neighbouring China and western Central Asia and showed some similarities to complexes like Tikal and Angkor. This article evaluates if those sites can be associated with low-density urbanism. Three selected sites, 尼雅 [Niya], 米兰 [Miran] and 樓蘭 [Loulan], have been evaluated for the presence of characteristic associated with low-density urbanism: dispersed monumental architecture, large scale anthropogenic landscapes modifications, and pattern of alternating housing clusters and agricultural fields. This can affect our understating of both the understanding of urbanism in the region and low-density urbanism on the global scale.